Cyanoacrylate for Intraoral Wound Closure: A Possibility? - Sagar, Parimala; Prasad, Kavitha; Lalitha, R. M.; Ranganath, Krishnappa (International Journal of Biomaterials, 2015)
Wound closure is a part of any surgical procedure and the objective of laceration repair or incision closure is to approximate the edges of a wound so that natural healing process may occur. Over the years new biomaterials have been discovered as an alternate to conventional suture materials. Cyanoacrylate bioadhesives are one among them. They carry the advantages of rapid application, patient comfort, resistance to infection, hemostatic properties, and no suture removal anxiety. Hence this study was undertaken to study the effect of long chain cyanoacrylate as an adhesive for intraoral wound closure and also to explore its hemostatic and antibacterial effects. Isoamyl-2-cyanoacrylate (AMCRYLATE) was used as the adhesive in the study. In conclusion isoamyl cyanoacrylate can be used for intraoral wound closure, as an alternative to sutures for gluing the mucoperiosteum to bone, for example, after impaction removal, periapical surgeries, and cleft repair. Its hemostatic and antibacterial activity has to be further evaluated.